Employment relations in the Asia Pacific : changing approaches (St Leonards, N.S.W. : Allen and Unwin, 2000)
Introduction. National perspectives. Perspectives on unions. Perspectives on companies. An international institutional perspective.
Keywords: Economics; Labor; Asia; Industry; Labor economics -- Asia; Industrial relations -- Asia; Industrial relations -- Pacific Area; Industrial relations -- Australia; Labor economics -- Pacific Area; Labor economics -- Australia